PRIMEIRO REGISTRO DE OCORRÊNCIA DE Onchoscelis germari BOHEMAN, 1837 (COLEOPTERA, CURCULIONIDAE) EM CAIXETA, Simarouba amara AUBL. (SIMAROUBACEAE), NO BRASIL - Peres Filho, Otávio; Dorval, Alberto; Moura, Rogério Goularte; Berti Filho, Evoneo (REVISTA DE AGRICULTURA, 2015)
PRIMEIRO REGISTRO DE OCORRÊNCIA DE Onchoscelis germari BOHEMAN, 1837 (COLEOPTERA, CURCULIONIDAE) EM CAIXETA, Simarouba amara AUBL. (SIMAROUBACEAE), NO BRASIL